Biomarkers and antithrombotic treatment in cervical artery dissection – Design of the TREAT-CAD randomised trial. (September 2020) - Traenka, Christopher; Gensicke, Henrik; Schaedelin, Sabine; Luft, Andreas; Arnold, Marcel; Michel, Patrik; Kägi, Georg; Kahles, Timo; Nolte, Christian H; Kellert, Lars; Rosenbaum, Sverre; Sztaizel, Roman; et al.
Introduction: The type of antithrombotic treatment in cervical artery dissection patients is still a matter of debate. Most physicians prefer anticoagulants over antiplatelet agents for stroke prevention. However, this approach is not evidence-based and antiplatelets might be as safe and as effective. The 'Biomarkers and Antithrombotic Treatment in Cervical Artery Dissection' ('TREAT-CAD') trial (clinicaltrials.gov: NCT02046460) compares Aspirin to oral anticoagulants (vitamin K antagonists) with regard to efficacy and safety by using both clinical and imaging surrogate outcome measures. TREAT-CAD tests the hypothesis, that aspirin is as safe and effective as vitamin K antagonists. Patients and methods: TREAD-CAD is a P rospective, R andomised controlled, O pen-labelled, multicentre, non-inferiority trial with B linded assessment of outcome E vents (PROBE-design). Key eligibility criteria are (i) clinical symptoms attributable to cervical artery dissection and (ii) verification of the cervical artery dissection diagnosis by established magnetic resonance imaging criteria. Patients are randomised to receive either Aspirin 300 mg daily or vitamin K antagonists for 90 days. Results: Primary outcomes are assessed at 14 ± 10 days (magnetic resonance imaging and clinical examination) and at 90 ± 30 days (clinical examinations). The primary endpoint is a composite outcome measure – labelled C erebrovascular I schemia, major H emorrhagic events or D eath (CIHD) – and includes (i) occurrence of any stroke (including retinal infarction), (ii) new ischaemic lesions on diffusion-weighted magnetic resonance imaging, (iii) any major extracranial haemorrhage, (iv) any symptomatic intracranial haemorrhage, (v) any new haemorrhagic lesion visible on paramagnetic-susceptible sequences and (vi) death. Discussion: After database closure, (i) central verification of cervical artery dissection diagnosis will be done by two experienced raters, (ii) adjudication of outcome events will be performed by independent adjudication committees, separately for clinical and imaging outcomes. The primary analysis will be done on the per protocol data set. The targeted sample size consists of 169 evaluable patients in the per protocol data set. Conclusion: TREAT-CAD is testing the non-inferiority of Aspirin versus vitamin K antagonists treatment in patients with symptomatic cervical artery dissection by combined clinical and magnetic resonance imaging outcomes.